Biodegradable medical implants: a new hope to reduce device-associated infections - José Carlos do Coito Paiva (2022)
Bone fractures often require fixation devices that frequently need to be surgically removed. These implants and procedures turn the patient more prone to develop medical device-associated infections, and osteomyelitis associated with trauma is a challenging complication for orthopedists. In recent years, biodegradable materials have gained great importance as temporary medical implant devices, avoiding removal surgery. The purpose of this systematic review was to revise the literature regarding the use of biodegradable bone implants in fracture healing and its impact on the reduction of implant-associated infections. The systematic review followed the PRISMA guidelines and was conducted by searching published studies regarding the in vivo use of biodegradable bone fixation implants and their antibacterial activity. From a total of 667 references, 23 studies were included based on inclusion and exclusion criteria. Biodegradable orthopedic implants of Mg-Cu, Mg-Zn, and Zn-Ag have shown antibacterial activity especially in reducing infection burden by MRSA strains in vivo osteomyelitis models. Their ability to prevent and tackle implant-associated infections and to gradually degrade inside the body reduces the need for a second surgery for implant removal, with expectable gains regarding patients' comfort. Further in vivo studies are mandatory to evaluate the efficiency of these antibacterial biodegradable materials.